2013
DOI: 10.1111/sltb.12038
|View full text |Cite
|
Sign up to set email alerts
|

Using the Suicide Index Score to Predict Treatment Outcomes among Psychiatric Inpatients

Abstract: For many suicidal people, the desire to die is moderated by a competing desire to live. This study aimed to demonstrate the ability of a wish-to-live versus wish-to-die index score to measure ambivalence and trichotomize suicidal inpatients into distinct stratified risk groups. Analyses revealed that index scores calculated for patients at treatment start significantly discriminated among the groups at index and uniquely predicted suicidal ideation, hopelessness, and depression scores across treatment. On aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…Assessment of suicidal ambivalence (i.e., both the wish to die and the wish to live) has successfully predicted future suicidal thoughts and behaviors, response to suicide treatment, and eventual suicide (O’Connor, Jobes, Yeargin, et al, 2012; Brown, Steer, Henriques, & Beck, 2005; O’Connor, Jobes, Comtois, et al, 2012; Lento, Ellis, Hinnant, & Jobes, 2013). We recommend that clinicians assess both reasons to live and reasons to die when calculating suicide risk and throughout treatment in order to monitor progress.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of suicidal ambivalence (i.e., both the wish to die and the wish to live) has successfully predicted future suicidal thoughts and behaviors, response to suicide treatment, and eventual suicide (O’Connor, Jobes, Yeargin, et al, 2012; Brown, Steer, Henriques, & Beck, 2005; O’Connor, Jobes, Comtois, et al, 2012; Lento, Ellis, Hinnant, & Jobes, 2013). We recommend that clinicians assess both reasons to live and reasons to die when calculating suicide risk and throughout treatment in order to monitor progress.…”
Section: Discussionmentioning
confidence: 99%
“…The measure has also been used to demonstrate meaningful differences in trajectories of recovery for suicidal individuals involved in psychotherapy (Lento, Ellis, Hinnant, & Jobes, ; S. S. O'Connor et al., ). The total score for the BSS reflects the severity of suicidal ideation, with higher scores indicating greater severity; overall, the measure demonstrated excellent internal consistency reliability (α = .97).…”
Section: Methodsmentioning
confidence: 99%
“…Previous test construction research has shown that the six SSF variables are quasi-independent and describe unique variance with factor structure reflecting acute and chronic suicidal states. Beyond this dichotomy however there are valuable wish to live versus wish to die ratings that can reliability differentiate distinct suicidal states (Lento, Ellis, Hinnant, & Jobes, 2013). Qualitative SSF prompts may also revelatory information that can inform treatment planning (Jobes & Mann, 1999; Jobes et al, 2004).…”
Section: Cams As a Possible Remedymentioning
confidence: 99%